AI-Assisted Feedback Bots in Pakistani ESP Classrooms: Improving Writing Proficiency and Learner Autonomy - Sumayyah Malik (Corresponding Author),; Dr. Salma Kalim, (Al-Qanṭara, 2025)
Purpose: This research explored the potential of the integration of AI-assisted feedback bots as a tool to enhance the writing proficiency of undergraduate ESP learners in Pakistan. Method: Utilizing a Mixed Methods Action Research approach, this study evaluated the impact of AI-assisted feedback bots on writing proficiency, demonstrated by the substantial increase in post-test scores. The qualitative content analysis highlighted the AI bot’s role in providing structured guidance, task-specific assistance and promoting learner autonomy, though some students preferred traditional feedback methods. Findings: The study concluded that AI-assisted feedback can serve as a valuable complement to traditional feedback methods, provided it is integrated thoughtfully.